How impulse buying influences compulsive buying: The central role of consumer anxiety and escapism. (July 2016) - Darrat, Aadel A.; Darrat, Mahmoud A.; Amyx, Douglas
Abstract: The paper highlights key research findings regarding compulsive buying behavior and aims at describing and testing the relationship between compulsive buying and an alternative buying phenomenon, i.e. impulse buying. Two common views of the relationship between compulsive and impulse buying are discussed and combined to form a hybrid conceptualization. Results suggest that impulse buying increases anxiety in consumers that is in turn, linked to compulsive buying. Notably, consumer escapism appears to deter the conversion of anxiety into compulsive buying. Results and managerial implications are discussed.